Importance of inspection to prevent structural pathologies in civil works (REMUNOM, 2025)
Structural pathologies in civil engineering represent one of the main challenges in engineering,compromising the safety, durability, and functionality of buildings. These pathologicalmanifestations can arise due to several factors, such as design flaws, execution errors,inadequate use of materials, lack of maintenance, and environmental actions. One solution to thisproblem is inspection. In view of this, the present study aimed to discuss the relevance ofinspection as a preventive tool against structural pathologies, analyzing its benefits and impactson the durability and safety of buildings. The methodology used was based on an integrativeliterature review, based on scientific articles, theses, and journals. Data collection was carried outthrough CAPES, Scielo, and Google Scholar databases, from 2019 to 2024. The results clearlyshow that efficient inspection reduces the occurrence of structural pathologies, as it ensures thattechnical standards and quality standards are correctly followed during all stages of construction.On the other hand, the lack of supervision or its inefficient execution increases the risk ofstructural failures, resulting in high corrective maintenance costs and putting user safety at risk.